2020
DOI: 10.1093/brain/awaa233
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology-validated recommendations for cortical lesion imaging in multiple sclerosis

Abstract: Cortical demyelinating lesions are clinically important in multiple sclerosis, but notoriously difficult to visualize with MRI. At clinical field strengths, double inversion recovery MRI is most sensitive, but still only detects 18% of all histopathologically validated cortical lesions. More recently, phase-sensitive inversion recovery was suggested to have a higher sensitivity than double inversion recovery, although this claim was not histopathologically validated. Therefore, this retrospective study aimed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 35 publications
0
46
0
Order By: Relevance
“…Cortical MS lesions are notoriously difficult to visualize, likely due to their small dimension, lower baseline myelination of the cortex, low-inflammatory phenotype, and partial volume effects with CSF. 80 At 3 T, a recent postmortem study showed that fewer than a quarter of histopathologically confirmed cortical lesions could be depicted in T2w fluid-attenuated inversion recovery (T2-FLAIR), DIR, or PSIR sequences, 62 and these rates are likely much lower in the clinical setting. Observations from postmortem studies suggest that UHF imaging enhances sensitivity for cortical lesion detection up to approximately 30% to 40%, depending on the lesion type 14 , 81 (Table 1 ).…”
Section: Magnetic Resonance Imaging At 7 Tmentioning
confidence: 99%
“…Cortical MS lesions are notoriously difficult to visualize, likely due to their small dimension, lower baseline myelination of the cortex, low-inflammatory phenotype, and partial volume effects with CSF. 80 At 3 T, a recent postmortem study showed that fewer than a quarter of histopathologically confirmed cortical lesions could be depicted in T2w fluid-attenuated inversion recovery (T2-FLAIR), DIR, or PSIR sequences, 62 and these rates are likely much lower in the clinical setting. Observations from postmortem studies suggest that UHF imaging enhances sensitivity for cortical lesion detection up to approximately 30% to 40%, depending on the lesion type 14 , 81 (Table 1 ).…”
Section: Magnetic Resonance Imaging At 7 Tmentioning
confidence: 99%
“…Phase sensitive inversion recovery (PSIR) imaging uses phase-sensitive reconstruction along with a T1weighted sequence to increase the range of signal intensities, which seems to improve detection of cortical lesions at 3T compared to DIR imaging (Sethi et al 2013;Sethi et al 2012). However, superiority of PSIR over DIR was not confirmed in recent post-mortem work using immunohistochemical stains (Bouman et al 2020). Very recently, a susceptibility-weighted image contrast that utilizes signal inversion (IR-SWIET) has been proposed as another promising avenue for cortical lesion visualization at 3T (Beck et al 2020).…”
Section: Mri Of Cortical Lesions At Clinical Field Strengthmentioning
confidence: 99%
“…Despite these efforts, prospective sensitivity remains poor at 3T (18-23% for DIR in post-mortem studies including histological validation (Seewann et al 2012;Bouman et al 2020)). Using multiple sequences for lesion segmentation increases lesion detection rates (Nelson et al 2008;Maranzano et al 2016), but further improvements for the in vivo depiction of cortical lesions are still warranted in order to accelerate correct diagnosis and management of the MS spectrum.…”
Section: Mri Of Cortical Lesions At Clinical Field Strengthmentioning
confidence: 99%
See 2 more Smart Citations